Students’ Attitude on the Use of Machine Translation in Japanese Language Class - Irawati Agustine; Kun Makhsusy Permatasari (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of the study was to determine student attitudes towards the use of machine translation in Japanese classes, especially in Writing 1 and IV classes. Machine Translation is considered an online resource in facilitating the translation process. The method used is descriptive qualitative. Data were taken from questionnaires distributed to students. Participants are semester II and semester IV students who receive Japanese Writing courses. This research activity was conducted at Darma Persada University, Jakarta. The data analysis technique used three stages, namely data reduction, data presentation and concluding. The results showed that students were dissatisfied with the use of machine translation. This means that the student's attitude is negative. However, machine translation is considered to be able to help complete the translation task more quickly, but the translation results are not in the context of the target language